THE INFLUENCE OF PRICES PROMOTION AND E-SERVICE QUALITY ON CUSTOMER REPURCHASE INTENTION OF TRAVELOKA: STUDY ON TRAVELOKA USERS IN INDONESIA - PUSPITA SARI, NITA DWI (Jurnal Ilmiah Mahasiswa FEB, 2019)
This study aims to determine the effect of Price Promotion and E-ServiceQuality through Efficiency, System Availability, Fulfillment, and Privacy onRepurchase Intention of Traveloka customers in Indonesia. This is an explanatoryresearch that explains the causal relationship between the variables described throughhypothesis testing.This study used a sample of 262 people who had made transactionsusing Traveloka application for the last 2 years, within the criterion between the agesof 19 and 34 years old. Hypothesis testing is done using t test or t-statistic value. Thedata analysis tool used is Partial Least Square (PLS) and assisted with SmartPLS3.2.7 software. The results of the analysis obtained in this study are four variables in this study, namely Price Promotion, Efficiency, Fulfillment and Privacy have a significantinfluence on Repurchase Intention of Traveloka customers with Fulfilment being thedominant variable; whereas, System Availability does not have significant influenceon repurchase intention of Traveloka customers. Keyword: Price Promotion, E-Service Quality, Repurshase Intention, Traveloka